1985
DOI: 10.1271/bbb1961.49.1405
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin I-converting enzyme inhibitor derived from an enzymatic hydrolysate of casein. II. Isolation and bradykinin-potentiating activity on the uterus and the ileum of rats.

Abstract: Inhibitors of angiotensin I-converting enzyme were isolated from an enzymatic hydrolysate of bovine casein. The amino acid sequences of these inhibitors were Phe-Phe-Val-Ala-Pro-Phe-Pro-Glu-Val-Phe-Gly-Lys (CEI12), Phe-Phe-Val-Ala-Pro (CEI5), and Ala-Val-Pro-Tyr-Pro-Gln-Arg (CEI^). CEI5 is a penta-peptide derived from the hydrolysate of CEI12 with proline-specific endopeptidase, and CEI^is a hepta-peptide derived from /2-casein. These inhibitors potentiated bradykinin in the contraction of the uterus and the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
76
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(78 citation statements)
references
References 1 publication
2
76
0
Order By: Relevance
“…In contrast, keratin waste also showed ACE inhibiting activity, but the mixture of horn and hoof was very weak. In the amino acid sequences of previously reported ACE inhibiting peptides, many peptides contained proline (Maruyama et al, 1985;Yokoyama et al, 1992;Yamamoto, 1997). Collagen contains large amounts of hydroxyproline as a constituent amino acid (Morimura et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, keratin waste also showed ACE inhibiting activity, but the mixture of horn and hoof was very weak. In the amino acid sequences of previously reported ACE inhibiting peptides, many peptides contained proline (Maruyama et al, 1985;Yokoyama et al, 1992;Yamamoto, 1997). Collagen contains large amounts of hydroxyproline as a constituent amino acid (Morimura et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Physiological functions were found to be present in peptides produced from proteins by enzymatic hydrolysis. Studies on the physiological functions of peptides reported HIV-1 protease inhibiting activity (Lee & Maruyama, 1998), angiotensin-I-converting enzyme (ACE) inhibiting activity (Maruyama & Suzuki 1982;Maruyama et al,1985;Yokoyawa et al, 1992) and antioxidative effects (Chen et al, 1995;Mosammat et al, 1999). It is important that peptides have ACE inhibiting activity, as this represses hypertension non-pharmacologically.…”
mentioning
confidence: 99%
“…These include peptides from ␣-zein (Miyoshi et al, 1991;Yano et al, 1996), bovine casein (Maruyama et al, 1985;Maruyama & Suzuki, 1982), chicken muscle (Fujita et al, 2000), dried bonito (Yokoyama et al, 1992), pepsin hydrolyzed Indonesian dried-salted fish (tuna) (Astawan et al, 1995), sour milk (Nakamura et al, 1995), sake and sake lees (Saito et al, 1994a, b), and soy sauce (Kinoshita et al, 1993). An overview of ACE inhibitory peptides derived from food proteins was well reviewed in two papers of Ariyoshi (1993) and Yamamoto (1997).…”
mentioning
confidence: 99%
“…In addition, natural substances that improve biological function are likely to be useful. In recent years, peptides that inhibit angiotensin I-converting enzyme (ACE), which is important in adjustment of blood pressure (Kawamura, 2006), and substances derived from dried bonito flakes (Yokoyama et al, 1992), tuna (Kohama et al, 1988), casein (Maruyama et al, 1985), lactic acid (Nakamura et al, 1995), egg yolk (Kaneda et al, 2006), laver (Saito and Ogino, 2005), sake and sake cake (Saito et al, 1994), and royal jelly (Tokunaga et al, 2004) have been examined and some have been commercialized as functional foods. For the prevention and treatment of hypertension, it is desirable that such products are available for regular intake in daily life at a low cost.…”
Section: Introductionmentioning
confidence: 99%